An analytical concordance of the verb, the negation, and the syntax in Egyptian coffin texts - Molen, Rami van der. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2005)
The present volume is the long-awaited concordance of the Egyptian coffin texts. It forms the sequel to A Hieroglyphic Dictionary of Egyptian Coffin Texts by the same author. In 1961 A. de Buck published his important seven-volume corpus Egyptian Coffin Texts . The importance of these texts is considerable for a variety of reasons; they are one of the most important literary texts of classical Egypt; the many variants greatly enlarge our understanding of grammar and linguistic structures; the coffin texts are magical texts, the effectiveness of which depended upon the exact reproductions of the original spells . In this concordance the various readings of each lemma are provided in transliteration into the Latin alphabet, which makes the concordance easily accessible for those unable to read hieroglyphs. The material is divided into the morphological categories of the verb; within each category the verbs are treated in alphabetical order.